UPAYA PENINGKATAN KUALITAS PELAYANAN PERIZINAN LEWAT INOVASI JEMPUT BOLA Kajian Deskriptif pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Semarang Provinsi Jawa Tengah - Sudrajat, Yayat (Jurnal Politik Pemerintahan Dharma Praja, 2019)
Efforts to Improve Licensing Service Quality through Ball Pick Up Innovation. Descriptive Study on the Office of Investment and One-Stop Services in Semarang Regency, Central Java Province. This research is intended to find out how the innovation of licensing services by picking up the ball in improving the quality of licensing services at the Semarang One-Stop Service of Investment and Integrated Services. Other objectives are to find out the factors that hamper the path of innovation in pick-up licensing services and to find out the efforts made by the Semarang District One-Stop Investment Service and Integrated Services to improve the quality of licensing services. In this study the author uses the theory of Basuki Johanes (2013: 179) who sees public service innovation from relative benefits, suitability, complexity, the possibility of observable experiments. The method used in this research is inductive descriptive. Data collection is done by using interview methods, documentation, and observation. Data analysis techniques used include data reduction, data presentation and conclusion drawing. The results of the study showed that in the implementation of the licensing service innovation, picking up the ball had already been running but not yet maximally. It should be noted again about the location in implementing the licensing service for picking up the ball. The limiting factor that arises is the limited number of apparatus resources, the lack of facilities that support the innovation of ball picking licensing services, implementation that is not in accordance with standard operating procedures and lack of public awareness about the importance of licensing